ANALISIS PENGARUH FAKTOR- FAKTOR PRODUKSI TERHADAP PENDAPATAN USAHATANI BAWANG MERAH DI DESA LAPANDEWA MAKMUR KECAMATAN LAPANDEWA KABUPATEN BUTON SELATAN - Alzarliani, Waode (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2018)
This research was conducted in Lapandewa Makmur Village of Lapandewa sub-district of South Buton Regency, which takes place from June to July 2015. The aims of this research were : 1) to know what the area of land, seed, fertilizer, tanager labor simulates significant effect on farm incomes onion; 2) whether a land area is a partially significant effect on farm incomes onion; 3) whether the seed is partially significant effect on farm incomes onion; 4) whether the fertilizer is partially significant effect on farm incomes onion; 5) whether the workforce is partially significant effect on farm incomes onion. The purpose of this research were; 1) to determine the effect of land seed fertilizer, and labor on the farm income of onion, 2) to determine the effect of land on onion farming income, 3) to determine the effec1 of seed on onion farming income, 4) to determine the effect of fertilizer on onion farming income, 5) to determine the effect of employment on onion farming income. The population in this research is the overall farmers who cultivate plants of onion totaling 160 people. The determination of samples was done by simple random sampling so that the number of samples obtained as many as 40 people. Furthermore, the data tabulated and analyzed by multiple linear regression analysis techniques to find out whether there is an influence of socio-economic characteristics of the respondent against the productivity of farmers in onion farming. The results of the analysis conducted regression equation Y = 628566.433 + 5166123.665X1 + 0.0821X2 + 13.646X3 - 0.103X4 + e; The results of the research suggest that there as significant factors of production on onion farming income with adjusted R Square at 0.514. This shows that the factors of production together have the same influence on onion farming income of 51.4% and the remaining 48.6% is influenced by other factors. The value of significance for land area (X1) =0.026; seeds (X2) = 0.893; fertilizer (X3) = 0.024; labor (X4) = 0.854. The value of the probability obtained each of these variables is smaller when compared to the significance or confidence level 5%> or 0.05 then it can be said of the variable land area and fertilizer have significant effect, while labor (X4) and seeds (X2) have not significantly affected the revenues of onion farming.  Keywords: revenue, costs of production, cocoa